2020
DOI: 10.1080/19490976.2020.1714401
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction increases protective gut bacteria to rescue lethal methotrexate-induced intestinal toxicity

Abstract: Methotrexate (MTX) is a typical chemotherapeutic drug that is widely used in the treatment of various malignant diseases as well as autoimmune diseases, with gastrointestinal toxicity being its most prominent complication which could have a significant effect on the prognosis of patients. Yet effective ways to alleviate such complications remains to be explored. Here we show that 30% dietary restriction (DR) for 2 weeks dramatically increased the survival rate of 2-month-old female mice after lethal-dose MTX e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…Preliminary evidence from our laboratory shows that antibiotic-induced disruption of the microbiota worsens MTX-induced mucositis, increasing MTX-mortality and impairing mucosal recovery. These results align with existing preclinical findings 9 and clinical risk factors, with antibiotic use prior to chemotherapy associated with increased GI-M severity. 10 Similarly, while probiotics have shown some benefits in mitigating the severity of MTX associated GI-M, 11 translational success is variable.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Preliminary evidence from our laboratory shows that antibiotic-induced disruption of the microbiota worsens MTX-induced mucositis, increasing MTX-mortality and impairing mucosal recovery. These results align with existing preclinical findings 9 and clinical risk factors, with antibiotic use prior to chemotherapy associated with increased GI-M severity. 10 Similarly, while probiotics have shown some benefits in mitigating the severity of MTX associated GI-M, 11 translational success is variable.…”
Section: Introductionsupporting
confidence: 88%
“…Contrary to our hypothesis, this did not affect the ability of pretherapy fasting to prevent MTX-induced GI-M, indicating that it is more likely that the lack of fat stores masks the protective cellular and microbial mechanisms induced by fasting. Despite the contradictory findings to those published by Tang et al, (2020) and Raffaghello et al, (2008), there are a number of differences that must be acknowledged. Firstly, both studies reporting positive effects of fasting/dietary modulation used lethal doses of chemotherapy administered to mice.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The disrupted intestinal barrier leads to intestinal LPS translocation into circulation [ 30 ]. Therefore, the gastrointestinal toxicity of MTX could result in loss of body weight ever increased mortality [ 31 ]. MSCs have been thought of as an effective method to alleviate different types of small intestinal injuries [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, dietary control offers a safer alternative herein. It was found that dietary restriction remarkably enhanced the survival rate of mice exposed to a lethal dose of MTX and ameliorated MTX-induced intestine inflammation with Lactobacillus rhamnosusplaying a critical role (Tang et al, 2020). In this case, dietary restriction needless of specific diet, drug, or probiotics intervened achieved remarkable results in reducing MTX-induced gastrointestinal side effects, suggesting what we eat, which constitutes the major part of gastrointestinal contents, probably determines therapeutic and toxic outcomes of orally administered drugs somehow.…”
Section: Methotrexatementioning
confidence: 94%